DETERMINATION OF OPTIMAL CAPACITIES OF BURNER FACILITIES IN HEATING FURNACES OF JET TYPE - I. A. Trusova; P. E. Ratnikov; D. V. Mendelev (Литьë и металлургия)
The results of numerical modeling of heating operation of furnace of the metal high-speed jet heating are given.